PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, KEBIJAKAN DIVIDEN, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Muhammad Safarrudin Afandi; Aries Jonathan (E-Jurnal Akuntansi TSM, 2022)
One of the goals of the company was established to maximize the value of the company. Firm value can be measured in various ways. This study aims to examine the effect of profitability, leverage, liquidity, dividend policy, managerial ownership, institutional ownership, and firm growth on firm value. The object in this study is to use manufacturing companies on the Indonesia Stock Exchange during year 2017 to year 2019. The purposive sampling method was used to select a sample of companies and 69 companies were selected and analyzed using the multiple regression method. The results show that dividend policy, profitability and institutional ownership have a positive effect on firm value, while leverage, liquidity, managerial ownership, and firm growth have no effect on firm value. These results imply that the greater the dividend policy ratio will increase investor confidence in earnings, high profitability indicates good company prospects in the future, and the greater the institutional ownership, the stronger the control over the company to achieve company goals and increase the firm value